Labile forms of carbon and soil aggregates - Erika Tobiašová; Gabriela Barančíková; Erika Gömöryová; Jarmila Makovníková; Rastislav Skalský; Ján Halas; Štefan Koco; Zuzana Tarasovičová; Jozef Takáč; Miroslav Špaňo (Soil and Water Research, 2016)
Soil organic matter (SOM) plays an important role in the soil aggregation and vice versa, its incorporation into the soil aggregates is one of the mechanisms of soil organic carbon stabilization. In this study the influence of labile carbon fractions on the fractions of dry-sieved (DSA) and wet-sieved (WSA) macro-aggregates and the relationship between the content of total organic carbon (TOC) and its labile fractions in the soil and in the fractions of macro-aggregates were determined. The experiment included six soil types (Eutric Fluvisol, Mollic Fluvisol, Haplic Chernozem, Haplic Luvisol, Eutric Cambisol, Rendzic Leptosol) in four ecosystems (forest, meadow, urban, and agro-ecosystem). In the case of DSA, the contents of labile fractions of carbon, in particular cold water extractable organic carbon (CWEOC) and hot water extractable organic carbon (HWEOC), had a higher impact on the proportions of larger fractions of macro-aggregates (3-7 mm), while in the case of WSA, the impact of labile fractions of carbon, mainly labile carbon (CL) oxidizable with KMnO4, was higher on the proportions of smaller fractions of aggregates (0.25-1 mm). The WSA size fraction of 0.5-1 mm seems an important indicator of changes in the ecosystems and its amounts were in a negative correlation with CL (r = -0.317; P < 0.05) and HWEOC (r = -0.356; P < 0.05). In the WSA and DSA size fractions 0.5-1 mm, the highest variability in the contents of TOC and CL was recorded in the forest ecosystem > meadow ecosystem > urban ecosystem > agro-ecosystem. The higher were the inputs of organic substances into the soil, the greater was the variability in their incorporation into the soil aggregates. The influence of the content of TOC and its labile forms on their contents in the DSA and WSA was different, and the contents of TOC and CL in the aggregates were more significantly affected by the CL content than by water soluble carbon. In the case of WSA fractions, their carbon content was more affected in the 1-2 mm than in 0.5-1 mm fraction.